Global research trends in traditional Chinese medicine therapy for acute leukemia: a comprehensive visualization and bibliometric analysis - Wenwen Zhang; Kaili Zhang; Yuqing Feng; Gaofeng Zhang (Hematology)
Background: The application of traditional Chinese medicine (TCM) therapy to acute leukemia has been intensively investigated. However, the bibliometric analysis in this field has not been performed. This bibliometric study aimed to comprehensively analyze the research trends and active areas of TCM therapy for acute leukemia from 2000 to 2023.Methods: We searched articles and reviews published between 2000 and 2023 that discussed TCM in acute leukemia from the Web of Science Core Collection (WoSCC). Knowledge mapping and bibliometric analysis were conducted using VOSviewer, CiteSpace software, and R-bibliometrix.Results: A total of 1,099 articles were included, with China, the United States, and Korea contributing the most papers. Most papers were published in the Journal of Ethnopharmacology. Meanwhile, China saw a steady increase in the number of publications. The three leading institutions that made outstanding contributions were the China Medical University, the Chinese Academy of Sciences, and the China Academy of Chinese Medical Sciences. Efferth Thomas, Liu Wei, and Liu Jie were the top three productive authors, with Efferth T receiving the most co-citations. The most frequently cited reference was Shen ZX (1997). In the analysis of keywords co-occurrence, ‘survival,’ ‘risk factors,’ ‘nanoparticles,’ and ‘metabolism’ are the active research topics.Conclusion: This bibliometric study provides researchers with a comprehensive overview and significant value in understanding the development of TCM in acute leukemia treatment.